(untitled) (Global Conference on Medical and Health Sciences, 2026)
Twin pregnancy is associated with an increased risk of maternal and perinatal complications compared with singleton pregnancy. Dichorionic diamniotic (DCDA) twins represent the most common type of twin gestation and generally have a more favorable prognosis than monochorionic twins. Nevertheless, DCDA pregnancies remain at higher risk for adverse outcomes, including preterm birth, hypertensive disorders, fetal growth abnormalities, and placental dysfunction. This review aims to compare the clinical course of DCDA twin pregnancies with singleton pregnancies and to identify the main maternal and fetal complications associated with multiple gestation.